Weed Control in Dryland Cropping Systems - Thompson, Curtis R.; Brown, Randall; O'Brien, Daniel M.; Sartwelle III, James; Schlegel, Alan (My University, 1998)
This publication describes weed control in dryland cropping systems for producers.
MF2339_1998_05
Keywords: MF2339; Crops; MF